2021
DOI: 10.3390/ijms222312767
|View full text |Cite
|
Sign up to set email alerts
|

L-NAME Administration Enhances Diabetic Kidney Disease Development in an STZ/NAD Rat Model

Abstract: One of the most important risk factors for developing chronic kidney disease (CKD) is diabetes. To assess the safety and efficacy of potential drug candidates, reliable animal models that mimic human diseases are crucial. However, a suitable model of diabetic kidney disease (DKD) is currently not available. The aim of this study is to develop a rat model of DKD by combining streptozotocin and nicotinamide (STZ/NAD) with oral N(ω)-Nitro-L-Arginine Methyl Ester (L-NAME) administration. Diabetes was induced in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…DKD was induced in rats by STZ and NAD injections combined with L-NAME administration, as previously reported [19]. The strength of this model was reconfirmed by the fact that all rats developed severe hyperglycemia, indicating the induction of diabetes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…DKD was induced in rats by STZ and NAD injections combined with L-NAME administration, as previously reported [19]. The strength of this model was reconfirmed by the fact that all rats developed severe hyperglycemia, indicating the induction of diabetes.…”
Section: Discussionsupporting
confidence: 72%
“…The present study aimed to compare the efficacy of metformin, canagliflozin, and a combination of both with quercetin with regards to the development and progression of DKD in rats. DKD was initiated by the induction of diabetes with streptozotocin (STZ) and nicotinamide (NAD), and combined with daily N(ω)-Nitro-L-Arginine Methyl Ester (L-NAME) administration, which further contributes to nephropathy development, as previously demonstrated by our lab [19].…”
Section: Introductionmentioning
confidence: 92%
“…L-NAME acts as a false substrate for endothelial nitric oxide synthase (eNOS), thus reducing the formation of nitric oxide (NO), resulting in the development of NO-deficient hypertension [14]. Besides the shortage of vasodilative action of NO itself, reduced NO availability in the renal artery is thought to stimulate renin release, followed by angiotensin II (Ang II)-aldosterone axis activation in the circulation [15] and in tissues such as the heart and aorta [16] or kidney [14,17], thus contributing to hypertension development and end-stage organ damage [15]. Nonetheless, our recent investigation revealed that L-NAME-induced hypertension is linked not to heightened, but rather to the normal or reduced activation of the renin-angiotensin II system (RAS) in both serum and LV tissue [18].…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological staining of kidney is also frequently used for the analysis of kidney injury in this NA-STZ animal model. Figure 3 and Figure 4 [ 48 , 49 ] show a typical staining of the kidney tissues by the periodic acid–Schiff and Masson trichrome, respectively. As can be observed from these histochemical stainings, the pathophysiological changes are obvious in the NA-STZ diabetic kidneys.…”
Section: Renal Pathophysiology In This Na/stz Animal Modelmentioning
confidence: 99%
“…Indicated are tubular epithelial cell necrosis (asterisk), thickening of tubular basement membrane (arrow). This figure was reproduced from Corremans et al [ 48 ].…”
Section: Figurementioning
confidence: 99%